AMPLITUDE-ONLY PATTERN NULLING OF LINEAR ANTENNA ARRAYS WITH THE USE OF BEES ALGORITHM - Guney, Kerim; Onay, Murat (Electromagnetic waves (Cambridge, Mass.), 2007)
An efficient method based on bees algorithm (BA) for the pattern synthesis of linear antenna arrays with the prescribed nulls is presented. Nulling of the pattern is achieved by controlling only the amplitude of each array element. Numerical examples of Chebyshev pattern with the single, multiple and broad nulls imposed at the directions of interference are given to show the accuracy and flexibility of the BA.